Dihydroergotamine inhibits the vasodepressor sensory CGRPergic outflow by prejunctional activation of α2-adrenoceptors and 5-HT1 receptors - Abimael González-Hernández; Jair Lozano-Cuenca; Bruno A. Marichal-Cancino; Antoinette MaassenVanDenBrink; Carlos M. Villalón (The Journal of Headache and Pain, 2018)
Abstract Background Dihydroergotamine (DHE) is an antimigraine drug that produces cranial vasoconstriction and inhibits trigeminal CGRP release; furthermore, it inhibits the vasodepressor sensory CGRPergic outflow, but the receptors involved remain unknown. Prejunctional activation of α2A/2C-adrenergic, serotonin 5-HT1B/1F, or dopamine D2-like receptors results in inhibition of this CGRPergic outflow. Since DHE displays affinity for these receptors, this study investigated the pharmacological profile of DHE-induced inhibition of the vasodepressor sensory CGRPergic outflow. Methods Pithed rats were pretreated i.v. with hexamethonium (2 mg/kg·min) followed by continuous infusions of methoxamine (20 μg/kg·min) and DHE (3.1 μg/kg·min). Then, stimulus-response curves (spinal electrical stimulation; T9-T12) or dose-response curves (i.v. injections of α-CGRP) resulted in frequency-dependent or dose-dependent decreases in diastolic blood pressure. Results DHE inhibited the vasodepressor responses to electrical stimulation (0.56–5.6 Hz), without affecting those to i.v. α-CGRP (0.1–1 μg/kg). This inhibition by DHE (not produced by the methoxamine infusions): (i) was abolished by pretreatment with the combination of the antagonists rauwolscine (α2-adrenoceptor; 310 μg/kg) plus GR127935 (5-HT1B/1D; 31 μg/kg); and (ii) remained unaffected after rauwolscine (310 μg/kg), GR127935 (31 μg/kg) or haloperidol (D2-like; 310 μg/kg) given alone, or after the combination of rauwolscine plus haloperidol or GR127935 plus haloperidol at the aforementioned doses. Conclusion DHE-induced inhibition of the vasodepressor sensory CGRPergic outflow is mainly mediated by prejunctional rauwolscine-sensitive α2-adrenoceptors and GR127935-sensitive 5-HT1B/1D receptors, which correlate with α2A/2C-adrenoceptors and 5-HT1B receptors, respectively. These findings suggest that DHE-induced inhibition of the perivascular sensory CGRPergic outflow may facilitate DHE’s vasoconstrictor properties resulting in an increased vascular resistance.